The impact of the COVID-19 pandemic on subjective mental well-being: The interplay of perceived threat, future anxiety and resilience - Paredes, Mario R.; Apaolaza, Vanessa; Fernandez-Robin, Cristóbal; Hartmann, Patrick; Yañez-Martinez, Diego (Personality and individual differences, 2021)
The COVID-19 pandemic has potentially a serious impact on many people's mental well-being. This study analyses the influence of the perceived threat of COVID-19 on subjective mental well-being with an online survey (n = 711). Findings confirmed the hypothesized model that provides a process explanation for this effect through the mediating influence of the activation of future anxiety. In addition, results confirmed that this influence via future anxiety is moderated by resilience, a personality trait that enables individuals to cope better with stressful or traumatic events. Individuals with higher levels of resilience compared to those with lower levels registered a lower impact of perceived Covid threat on future anxiety and, in turn, on subjective well-being. This study contributes theoretically to a better understanding of the factors that determine the impact of traumatic events such as a pandemic on people's mental health. The implications of this study indicate interventions that may be carried out to minimize the pandemic's negative psychological consequences. •Perceived threat of COVID-19 has a negative impact on subjective mental-wellbeing.•Future anxiety mediates the influence of Covid threat on mental well-being.•Resilience moderates negatively the effect of Covid threat via future anxiety.•Resilient individuals are less susceptible to Covid's mental health impact.